2013
DOI: 10.1038/srep02252
|View full text |Cite
|
Sign up to set email alerts
|

Molecular logistics using cytocleavable polyrotaxanes for the reactivation of enzymes delivered in living cells

Abstract: The intracellular delivery of enzymes is an essential methodology to extend their therapeutic application. Herein, we have developed dissociable supermolecule-enzyme polyelectrolyte complexes based on reduction-cleavable cationic polyrotaxanes (PRXs) for the reactivation of delivered enzymes. These PRXs are characterized by their supramolecular frameworks of a polymeric chain threading into cyclic molecules, which can form polyelectrolyte complexes with anionic enzymes while retaining their three dimensional s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 44 publications
(62 reference statements)
0
21
1
Order By: Relevance
“…Several authors, including our group, reported previously that cationic polyelectrolytes can bind to anionic enzymes, resulting in inhibition of enzyme activities . However, the results of the present study showed that the enzyme activity of ASNase did not change despite PPC formation (Fig.…”
Section: Discussioncontrasting
confidence: 67%
“…Several authors, including our group, reported previously that cationic polyelectrolytes can bind to anionic enzymes, resulting in inhibition of enzyme activities . However, the results of the present study showed that the enzyme activity of ASNase did not change despite PPC formation (Fig.…”
Section: Discussioncontrasting
confidence: 67%
“…The PRXs are supermolecules that consist of α‐cyclodextrins (CDs) threaded along a poly(ethylene glycol) (PEG) chain capped with terminal bulky stopper molecules . We have designed functionalized PRXs bearing carboxylic acids, tertiary amino groups, biotins, and peptide ligands for the interaction, binding, and complex formation with proteins . Because the functional groups modified at the α‐CD moieties in PRXs are freely mobile along the PEG axle, they can improve steric hinderance in multivalent interactions to facilitate binding and complex formation with proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Taking advantage of this non‐covalent character of PRXs, we have developed biocleavable PRXs bearing intracellularly cleavable linkages, such as disulfide and enzymatically cleavable peptides, to exert stimuli‐responsive dissociation of PRXs . Previously, we have designed tertiary amino groups‐modified biocleavable PRXs to form a polyelectrolyte complex with anionic biomolecules such as plasmid DNA (pDNA), small interfering RNA (siRNA), and enzymes . These polyelectolyte complexes internalize into cells through endocytosis and undergo the dissociation of the complexes in response to the intracellular stimuli such as acidic pH and the reaction with intracellular reductant .…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we have designed tertiary amino groups‐modified biocleavable PRXs to form a polyelectrolyte complex with anionic biomolecules such as plasmid DNA (pDNA), small interfering RNA (siRNA), and enzymes . These polyelectolyte complexes internalize into cells through endocytosis and undergo the dissociation of the complexes in response to the intracellular stimuli such as acidic pH and the reaction with intracellular reductant . This stimuli‐dependent cleavage of PRXs exerts the release of biomolecules from the complexes, leading to enhancing their biological activity under intracellular conditions .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation